Journal of Business Venturing 2024 year in review: The year of exercising entrepreneurial agency in response to crises - Branzei, Oana; McMullen, Jeffery S.; Newbert, Scott L.; Schwens, Christian (Journal of Business Venturing, 2025)
When various forms of crisis hit, they can stimulate changes in entrepreneurial agency – the capacity to act (or choose not to) – and the actions entrepreneurs take to mitigate the threats and pursue the new opportunities those crises create. While assessing articles for the Journal of Business Venturing's annual “Best Paper” award, we observed this to be a recurring theme across a significant number of the studies published in 2024. Inspired by this research, we summarize the 17 articles that explored this theme and develop a framework that highlights material, relational, and discursive concerns brought about by crises. In response entrepreneurs across individual or collective levels take action to preserve or cultivate distinct forms of entrepreneurial agency – adaptive, allied, and censored – and to resolve various paradoxes of entrepreneurial agency. We close with a brief discussion of the growing relevance of a social symbolic lens in reconciling how entrepreneurs construe and respond to crises and how the specific forms of agency and paradox identified could inform theory both within and beyond entrepreneurship. Executive summary This article began as a search for the “Best Paper” published in Journal of Business Venturing (JBV) in 2024. The editor-in-chief selected a panel of editors who then reviewed each of the 49 articles published in volume 39, issues 1–6, to identify those that were bold, broad, and rigorous. We arrived at a shortlist of five articles that best exemplified these criteria, from which the entire JBV editorial team voted for the winner: “Sight unseen: The visibility paradox of entrepreneurship in an informal economy,” by Robert Nason, Siddharth Vedula, Joel Bothello, Sophie Bacq, and Andrew Charman. In addition to enabling the selection of a best paper, this process revealed a common theme cutting across more than one-third of the articles published throughout the year; namely, “how entrepreneurs exercise agency in response to crises.” Traditionally, crises have been defined as periods of turmoil that disrupt patterns of economic activities and represent acute potential threats to the livelihoods of those affected. Over the past decade, however, scholars (both within and outside the field of entrepreneurship) have gradually shifted attention from single, separate, and short-lasting episodes that momentarily disrupt entrepreneurial endeavors (Doern et al., 2016) to plural, entangled and long-lasting combinations, sometimes referred to as poly-crises (Klyver and McMullen, 2025). To consider both conceptualizations, we take a broader perspective of crisis, using the term holistically to include both acute and enduring widespread structural challenges. We reason that, by defying conformity and attempting actions that question a society's taken for granted assumptions about how the world works, entrepreneurs embody and enact a paradox of agency in which restrictions on their capacity to act – which dispirit, discourage, or even devastate most people – instead stimulate them to seek to preserve or cultivate their agency not only by mitigating the threats that crises can pose, but also by leveraging them as opportunities to improve their situation. We proceed as follows. After a brief introduction, we summarize how each individual article reflects and contributes unique insights to the overarching theme of exercising entrepreneurial agency in response to crises. Grouping the articles according to the type of crisis examined, we sensitize ourselves to the underlying mechanisms that entrepreneurs use in response by adopting a social symbolic lens (Lawrence and Phillips, 2019). Specifically, we hone our attention to the relative importance and interplay of material, relational, and discursive dimensions of social symbolic work as entrepreneurs construe and respond to different types of crises. We suggest that entrepreneurs encounter various limitations to and paradoxes of agency that they seek to resolve by adapting, allying, or censoring their capacity to act. Finally, we conclude by articulating potential avenues for scholars to elaborate on this tri-dimensional approach to entrepreneurial agency both within and beyond entrepreneurship theory and practice.